2009
DOI: 10.1093/arclin/acp077
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Mini-Mental State Exam with Culturally Deaf Senior Citizens

Abstract: The Mini-Mental State Exam (MMSE) is commonly used to screen cognitive function in a clinical setting. The measure has been published in over 50 languages; however, the validity and reliability of the MMSE has yet to be assessed with the culturally Deaf elderly population. Participants consisted of 117 Deaf senior citizens, aged 55-89 (M = 69.44, SD = 8.55). Demographic information, including state of residence, age, and history of depression, head injury, and dementia diagnoses, were collected. A standard for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…The repetition section of the Folstein MMSE is particularly problematic when being translated into American Sign Language. Due to grammatical differences between English and American Sign Language, a study by Dean et al (2009) found that only 21.4% of healthy older deaf signers could repeat the English idiom “No ifs, ands, or buts.” This is an example of differences between English and ASL that prevents direct word for word translation. However, our patient also was unable to repeat other sentences as described above.…”
Section: Discussionmentioning
confidence: 99%
“…The repetition section of the Folstein MMSE is particularly problematic when being translated into American Sign Language. Due to grammatical differences between English and American Sign Language, a study by Dean et al (2009) found that only 21.4% of healthy older deaf signers could repeat the English idiom “No ifs, ands, or buts.” This is an example of differences between English and ASL that prevents direct word for word translation. However, our patient also was unable to repeat other sentences as described above.…”
Section: Discussionmentioning
confidence: 99%
“…A scoring system of 3 points scale was then put to present the degree of exposure and adequacy. General subjective life stresses, life pattern to evaluate general activity and history of exercising were recorded and put on the 3 points scale [ 27 ].…”
Section: Materials Methods and Subjectsmentioning
confidence: 99%
“…The Mini-Mental State Examination (MMSE) was performed for clinical evaluation of mental and cognitive status. The 30-point questionnaires take between 5 and 10 minutes and examination functions including registration, attention, calculation, recall, language, commands, and orientation [44]. It is a sensitive, valid, and reliable method that is used extensively in clinical and research settings to measure cognitive impairment and to estimate the severity and progression of cognitive impairment.…”
Section: Cognitive and Mental Evaluationsmentioning
confidence: 99%